The Predictive Ability of Goal-Orientations in Academic Risk-Taking among Governmental School Students - العزام سوسن; Abu Ghazal, Muawiyah (Jordan Journal of Educational Sciences, 2025)
Objectives: This study aimed to investigate the predictive ability of goal orientations in academic risk- taking among students in public schools. Methods: The study adopted the descriptive correlational approach, the sample of the study consisted of 973 male and female students from public schools in Irbid City, selected using convenience sampling according to gender and grade. To achieve the study’s objectives, the Clifford scale for academic risk-taking and the Murayama and Elliot scale for goal orientations were administered. Results: The results showed that the level of academic risk- taking was moderate. There were no statistically significant differences in academic risk attributed to the gender variable, there were statistically significant differences attributed to the grade variable in favor of first-year secondary students. Additionally, a statistically significant predictive ability for the independent predictor of goal orientations, with the dependent predicted variable being academic risk-taking. The results indicated that the first predictors were mastery/approach goals, and the second were performance/approach goals, which statistically significantly explained 24.60% and 4.60%, respectively) of the variance in academic risk among governmental school students. Conclusion: The study recommended the necessity of encouraging students to adopt mastery/approach goals, as they play a role in increasing academic risk-taking, explaining 24.60% of the variance in academic risk-taking. Keywords: Predictive ability, Academic risk-taking, Goal orientations, Governmenta school students.